Pengaruh Strategi Lintasan Pahat; Raster Dan 3D Offset Terhadap Kerataan Dan Kesejajaran Produk - Cahyati, Sally (MESIN, 2007)
The Influence of Tool Path Strategies; Raster and 3D Offset to Flatness and Parallelismof Product. Parallelism of two surfaces is one of geometrical tolerance that can measure after theirtolerances offlatness are known. The parallelism andflatness are two geometrical characters thatusually require bystandardizedplates ofmould. Tool path ofmilling machine ona surface plateis one ofthing that influences their character. In this paper, geometrical character offlat plane surface that hadbeen machined by raster tool path strategy and 3D offset strategy will be analyzed. The result ofexperiment can beusefor refinement ofmachining strategies toachieve an optimized machining.